GeoStride: GPS-integrated safety boots - Che Nafiah, Ainul Aqilah; Kamaruding, Musmuliadi; Zuhairee, Adila Syakhira; Norizlanin, Nurfarah Aina; Ghazali, Nurammaroh Aisyah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
GPS-integrated safety boots from GeoStride effectively address the critical workplace safety gap by combining real-time location tracking with advanced protective footwear. Aiming primarily at the construction, mining, and manufacturing industries, these boots contain an SOS button and a GPS module, enabling instant emergency response. One of the product's significant innovations is using eco-friendly materials, consisting of microfiber leather, ergonomic insoles, and lightweight composite toe caps, providing comfort, durability, and sustainability. The survey findings from 42 respondents show that GeoStride features were strong points, with almost 82% admitting a need for real-time tracking and 73.8% pointing out the SOS button. Despite battery life, durability, and the privacy issues mentioned, the unique functionality and design details of GeoStride certainly enable it to be regarded as a trendsetter in the field of security innovation. Features include mobile app integration, pro-aesthetics, and several customization options, making the product even more appealing. GeoStride is the emblem of the future of the equipment that provides personal protection by assuring worker safety, elevating productivity, and upholding sustainable practices. This cutting-edge product, propelling us into a new era of occupational safety, will, however, be in a class of its own by being up to date with the recent advances in technology and the environment.